Analisis Tingkat Kepuasan Konsumen Terhadap Pelayanan Dapur Kopi Di Kelurahan Buha Kecamatan Mapanget Kota Manado - Tatukode, Marlinda Felia; Waney, Nordy Fritsgerald Lucky; Rumagit, Grace Adonia Josefina (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the level of customer satisfaction in the Coffee Kitchen service in Buha Village, Mapanget District, Manado City. This research was conducted from November 2022 to January 2023. The data used are primary and secondary data. Primary data is data interviewed directly conducted to consumers who visit Dapur Kopi. Secondary data is the collection of data in the form of data obtained from sources, namely literature such as books, journals, and previous research results. The sampling method uses the technique of determining Accidental Sampling , which is anyone who comes by chance. The number of respondents taken in this study was 40 people using the Slovin formula. The data analysis used in this study was descriptive data analysis using Likert Scale measurements. Based on research shows that the overall analysis of the level of customer satisfaction in the Coffee Kitchen service in Buha Village, Mapanget District, Manado City starts from the variables Price, product, place, reliability, responsiveness, assurance, empathy, direct evidence classified as satisfied with the satisfaction index in service 79.03%.